Types of Male Adolescent Violence Against Women in Three Contexts: Dating Violence Offline, Dating Violence Online, and Sexual Harassment Online Outside a Relationship - Díaz-Aguado, María José; Martínez-Arias, Rosario (Frontiers in Psychology, 2022)
There has been little investigation of male adolescent violence against women as acknowledged by boys themselves, and even less on such violence in different contexts with comparative studies of behavior between those who perpetrate this violence and the population at large. This study used cluster analysis to establish a male adolescent typology based on boys’ self-reporting of violence against women in three contexts. The participants were 3,132 Spanish teenage boys aged 14 to 18 with experience of relationships with girls. Three discrete, identifiable types were obtained: the first group (69.8%), of non-violent boys; the second group (26%), more involved in sexual harassment online outside a relationship but with a low incidence of dating violence offline; the third group (4.2%), with abuse in the three contexts but less involved in sexual harassment online than the second group. The logistic regression analysis showed that justification of male dominance and violence was the main risk condition for inclusion in the second and third groups, followed by low self-esteem (for the third group) and risky sexual behaviors online (for the second and third groups). The findings based on these results are important for preventing male adolescent dating violence against women in the three male types detected.